2018
DOI: 10.1098/rsif.2017.0380
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel biomaterials and their therapeutic potential for muscle injuries and muscular dystrophies

Abstract: Muscular diseases such as muscular dystrophies and muscle injuries constitute a large group of ailments that manifest as muscle weakness, atrophy or fibrosis. Although cell therapy is a promising treatment option, the delivery and retention of cells in the muscle is difficult and prevents sustained regeneration needed for adequate functional improvements. Various types of biomaterials with different physical and chemical properties have been developed to improve the delivery of cells and/or growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 187 publications
0
67
0
2
Order By: Relevance
“…Contractile cells and their precursors are especially sensitive to the mechanical properties of the substratum as their activity and maturation can be significantly impaired by stiff substrates, characterized by higher than those of healthy muscle tissues (12 kPa), that is, 133.2 MPa stiffness (Romanazzo et al, ). Most of the materials used to study the behavior of muscle cells belong to the hydrogel and elastomer group characterized by elastic modulus within the range of 0.1–100 kPa (Lev & Seliktar, ). However, it has been shown that myogenic cells can also survive on materials with much higher stiffness (Palchesko, Zhang, Sun, & Feinberg, ; Romanazzo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Contractile cells and their precursors are especially sensitive to the mechanical properties of the substratum as their activity and maturation can be significantly impaired by stiff substrates, characterized by higher than those of healthy muscle tissues (12 kPa), that is, 133.2 MPa stiffness (Romanazzo et al, ). Most of the materials used to study the behavior of muscle cells belong to the hydrogel and elastomer group characterized by elastic modulus within the range of 0.1–100 kPa (Lev & Seliktar, ). However, it has been shown that myogenic cells can also survive on materials with much higher stiffness (Palchesko, Zhang, Sun, & Feinberg, ; Romanazzo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were spread at the injection site, exhibiting striation of sarcomeric actinin and connexin 43, indicating on their physiological state and ability to form interactions with their close surroundings (Figure 7d,e). These can be attributed to the protective and supportive nature of the hydrogel, allowing the cells to interact with each other and with the ECM fibers until interactions with the host are made …”
Section: Resultsmentioning
confidence: 99%
“…These can be attributed to the protective and supportive nature of the hydrogel, allowing the cells to interact with each other and with the ECM fibers until interactions with the host are made. [25]…”
Section: Injection Of the Cellular Dropletsmentioning
confidence: 99%
“…Konigsberg long pointed out the importance of the extracellular matrix (ECM) protein collagen as a critical component to the development of muscle colonies, which led to its widespread use in SMTE . Since then, other natural and synthetic materials such as fibrin, alginate, polycaprolactone (PCL)‐based polymers, and various strategies have been developed to generate skeletal muscle tissues in vitro. Especially, the engineering of muscle fibers in vitro requires the culture of myoblasts in an anisotropic environment, promoting their alignment, favoring their fusion and the myogenesis .…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…[60,61] The development of bioinks is an active research area, and especially for SMTE, the development of hydrogel-based bioinks is well adapted ( Table 1). [24,[62][63][64] Natural and synthetic polymers have been used for the development of bioinks for bioprinting skeletal muscle constructs. Thus, among natural polymers, fast crosslinking hydrogels such as calcium alginate or fibrin have been used directly as bioink or as a supporting polymer during printing process in order to maintain the printed shape of less stable bioinks.…”
Section: Bioink Formulationsmentioning
confidence: 99%